A Pragmatic Definition of the Concept of Theoretical Saturation. Issue 2 (3rd April 2019) - Low, Jacqueline
ABSTRACT: In this article I critically discuss the concept of theoretic saturation, first presented by Glaser and Strauss in their classic book The Discovery of Grounded Theory . Over my almost two-decade career of using, researching, and publishing on qualitative methods, I have lost count of the number of qualitative researchers that have defined saturation as an instance where "no new information" emerges from data analysis. I argue that such a definition is problematic. It provides no didactic guidance on how researchers can determine such a point, and it is a logical fallacy, as there are always new theoretic insights as long as data continue to be collected. Finally, much new work on saturation focuses on how many interviews are required to reach it rather than developing definitions of what it is. In response I present what I argue is a more cogent and pragmatic definition of theoretic saturation.